Comparative ultrastructure of caryopsis and leaf surface anatomy in wild rice Oryza coarctata and O. rufipogon through Scanning Electron Microscope (SEM) - Subhas Chandra Roy; Anurag Chowdhury (Open Journal of Plant Science - Peertechz Publications, 2021)
The wild rice Oryza coarctata (Roxb.) is an herbaceous halophytic plant belongs to the grass family poaceae prevalent to the coastal regions of Southern Asia. The O. coarctata is the only hydro-halophytic rice germplasm under the genus Oryza and shows high salinity. Caryopsis ultrastructure of O. coarctata was compared with another wild rice O. rufipogon through Scanning Electron Microscopy (SEM) including leaf surface anatomy to unveil the differentiation between the two species of Oryza. In O. rufipogon, embryo is small and orthodox type with long viability, in O. coarcata, embryo is large size and recalcitrant type. In O. coarctata, lower part of the spikelet has callus and expanded disc-like structure, without any globose rachilla, lemma devoid of tubercles, prickles and microhairs. Leaves of O. coarctata contain salt hairs and salt glands to secrete excessive salt, during high salt concentration which is a most important characteristic of this halophytic wild rice. Caryopsis endosperm contains starch granule of spherical shape with protein bodies in O. coarctata, whereas polygonal or hexagonal with moderate angularity starch granule in O. rufipogon. Aleurone layer is not so distinct in O. coarctata in compared to O. rufipogon, where it is clear and distinct. Protein profiling was studied through SDSPAGE for banding pattern variation analysis. This study of rice caryopsis ultrastructure and leaf surface anatomy including salt-hairs will contribute to the knowledge about the conservation of such precious germplasm of Sudarban mangrove region for the improvement of climate resilient rice varieties in future through pre-breeding and transgenic system.